2019
DOI: 10.3892/mmr.2019.10741
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR‑138‑5p promotes non‑small cell lung cancer progression by regulating CDK8

Abstract: dysregulation of micrornas (mirnas) is frequently observed during cancer development. aberrant expression of mirna-138-5p (mir-138-5p) has been found in many types of cancer. However, the role and the mechanisms underlying mir-138-5p function in non-small cell lung cancer (nSclc) progression remain unknown. in the present study, miR-138-5p expression was identified to be decreased in tumor tissues compared with matched normal tissues from patients with nSclc. in addition, low expression of mir-138-5p was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Therefore, we predicted the latent miRNAs of MIR4435-2HG, and we found that miR-138-5p had specific binding sites with MIR4435-2HG through LncBase and starBase. MiR-138-5p is differentially expressed in various tumors, such as lung carcinoma ( 38 ), colon carcinoma ( 39 ), cervical carcinoma ( 40 ), and pancreatic carcinoma ( 41 ). And some researchers have found that ( 42 ) miR-138-5p can hinder the proliferation and invasion of gastric carcinoma by mediating epidermal growth factor receptor (EGFR).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we predicted the latent miRNAs of MIR4435-2HG, and we found that miR-138-5p had specific binding sites with MIR4435-2HG through LncBase and starBase. MiR-138-5p is differentially expressed in various tumors, such as lung carcinoma ( 38 ), colon carcinoma ( 39 ), cervical carcinoma ( 40 ), and pancreatic carcinoma ( 41 ). And some researchers have found that ( 42 ) miR-138-5p can hinder the proliferation and invasion of gastric carcinoma by mediating epidermal growth factor receptor (EGFR).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that CDK8 serves as a critical oncogenic molecule in various types of human cancer, including colorectal, breast and prostate cancer ( 50 52 ). Although the majority of studies support the oncogenic role of CDK8, a number of studies have indicated that CDK8 exerts repressive functions in different types of cancer, including colon ( 53 ), breast ( 54 , 55 ), pancreatic ( 56 ) and non-small cell lung ( 57 ) cancer. The context-specific roles of CDK8 in distinct types of human cancer have received increasing interest and there is considerable controversy regarding the development of CDK8-based therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…All of the miRNAs- miR-137, miR-186-5p, miR-214-3p, miR-129-5p, miR-185, miR-107 and let-7 correlated with CDK6 expression in their respective tumor suppressive pathways [ 89 , 95 , 96 , 97 , 98 ]. MiR-138-5p has been found as the only miRNA regulating CDK8 in suppressing NSCLC [ 99 ]. In terms of Cyclins being regulated, Cyclin D1 was found to be regulated the most as miR-202, miR-206, miR-15, miR-9-5p, miR-15a, miR-16-5p, miR-193a-3p, miR-193b, miR-186, miR-545 and miR-146a-5p have been demonstrated impacting Cyclin D1 in their tumor suppression mechanism of lung cancers [ 7 , 89 , 93 , 100 , 101 , 102 , 103 , 104 ].…”
Section: Involvement Of Deregulated Oncomirna or Tumor Suppressor Mir...mentioning
confidence: 99%